Information quality, homophily, and risk propensity: Consumer responses to online hotel reviews - Sony Kusumasondjaja (Universitas Hayam Wuruk Perbanas, 2015)
Searching through online review sites becomes an alternative for consumers to obtain product information. The efficiency and effectiveness in finding quality information on the online review sites contributes to the popularity of online review sites among consumers at the moment. There are some previous studies discussing consumer trust on hotels being reviewed on online review sites, but the roles of information quality, homophily, and consumer risk propensity as antecedents of trust and online purchase intention are still questionable. The purpose of this study is to investigate how information quality, homophily, and consumer risk propensity affect consumer trust on hotels being reviewed on online review sites and on intention to make a reservation. A survey involving 430 young travelers from 16 countries was conducted in popular tourist destination. Results confirm that information quality influences consumers’ trust on hotel being reviewed and intention to make reservation. Moreover, consumer online trust is also found to affect intention to make reservation.